Students' modeling of friction at the microscopic level - Corpuz, Edgar De Guzman (Kansas State University, 2006)
Research that investigates the dynamics of knowledge construction by students as they model phenomena at the microscopic level has not been extensively conducted in physics and science education in general. This research wherein I investigated the dynamics of knowledge construction of students in the context of microscopic friction is an attempt to do so. The study commenced with an investigation of the variations in the existing models of students about microscopic friction (phase I of the study). Clinical interviews were conducted with introductory physics students in order to elicit their models. A phenomenographic approach of data analysis was employed to establish the variations in students’ models. Results show that students’ mental models of friction at the atomic level are dominated by their macroscopic experiences. Friction at the atomic level according to most students is due to mechanical interactions (interlocking or rubbing of atoms). Can we build on these macroscopic ideas of students in order to help them construct more scientific explanations of friction at the atomic level? The second phase of the research was an investigation of the dynamics of knowledge construction of students as they constructed models of friction at the atomic level while building on their prior ideas. Individual as well as group teaching interviews were conducted with introductory physics students in order to investigate students learning trajectories and the processes they undergo as they created new models of friction at the atomic level. Results show that the span, zone of proximal development and the epistemological orientations of the students greatly influenced the extent to which they utilize scaffolding afforded to them during the model-building process. Moreover, results show that students undergo the process of incorporation and displacement during their model construction and reconstruction. In the third phase, an instructional material geared towards helping students develop more scientific explanations of microscopic friction was developed and pilot-tested. Overall, the results of the study have significant implications for further research, in improving instruction, and curriculum material development.
Keywords: Physics education; Modeling; Conceptual change; Microscopic modeling; Physics, General (0605)